Infection associated hemophagocytic lymphohistiocytosis: An institutional experience (Asian Journal of Medical Sciences, 2019)
Background: Hemophagocytic lymphohistiocytosis is an uncommon yet potentially life-threatening disorder. Even though an early recognition of this condition is critical, the diagnosis is often delayed due to a lack of awareness, as well as lack of specific clinical and laboratory features. There is no gold standard for confirmation of a suspected case of HLH.Aims and Objectives: In this article, we share our experience in infection-associated HLH, in the light of a thorough literature search.Materials and Methods: We analyzed the clinico-pathological features of 11 consecutive patients who were admitted to our hospital from July 2017 to January 2019 with a diagnosis of HLH. Bone marrow material was collected from all but one case, and the marrow aspirate and biopsy were studied in detail.Results: There were 9 adult and 2 pediatric patients with HLH. The infections associated with HLH were Dengue fever, Influenza B, and Adenovirus infection. One child had features of severe sepsis, but the causative agent was not identified. Eight out of 11 patients succumbed to the illness.Conclusion: This study highlights the high mortality rate related to infection associated HLH. Timely diagnosis and early aggressive treatment can improve the clinical outcome of this otherwise potentially fatal condition. Physicians should have a high index of suspicion when patients develop prolonged fever associated with cytopenia and multi-organ involvement.